‘L2 assessment and testing’ teacher education: an exploration of alternative assessment approaches using new technologies - Papadima-Sophocleous, Salomi (My University, 2017)
Most Second Language (L2) Teacher Training Assessment and Testing courses focus on testing. Through the development of a Master of Arts (MA) in a computer assisted language learning module (based on a constructivist and ‘practise what you preach’ approach, entailing that the teachers experience firsthand the assessment types they were asked to develop), the instructor/researcher aimed to provide Computer Assisted Language Assessment and Testing (CALAT) teacher education, focusing on classroom assessment. The module was based on (1) current theories and practices; (2) participants’ earlier assessment and testing background experiences as school students, and their assessment and testing experiences and current practices as L2 teachers; (3) participants’ assessment experiences not as L2 teachers but as students of the MA assessment and testing module; (4) participants’ L2 CALAT practising needs; and (5) problem-solving by constructing assessments suitable for their practising needs. This article draws on a small-scale questionnaire, participant in- and on-action reflective journal entries, and webinar chat notes to examine the extent to which these goals were achieved. Data analysis and discussion reveals that, the hands-on, technology-based, constructivist, and reflective approach applied enhanced participants’ knowledge, skills and experiences in CALAT in general and in L2 classroom assessment in particular.
Keywords: Computer assisted language assessment and testing; CALAT; Teacher education; Learner perceptions